Fixed rate loan contracts, maturity transformation and competition in the deposit market - Matti Suominen (Bank of Finland, 1993)
This paper suggests that the optimal contract in lending under asymmetric information is a fixed rate loan contract. It is shown that deposit banks have an advantage to provide maturity transformation with fixed rate contracts. This is because the spatial nature of deposit market competition makes the oligopolistic cooperation likely. Cooperation, on the other hand, provides banks more stable funding when depositors derive utility from both monetary compensation (interest) and the proximity of banks services. lt is also shown that by committing in loan markets to fixed rate returns banks can reduce their incentives to compete over deposits.
URN:NBN:fi:bof-201908121392
Keywords: 330